ENCAPSULATION RESPONSE FROM THE HEMOCYTES OF ESTUARINE CLAM MERETRIX CASTA - B.MEENA,; SUMIT ROSE,; S.S. JAYARAJ,; S.VINCENT, (International Journal of Pharma and Bio Sciences, 2010)
The encapsulation response of hemocytes was specific towards the positively charged DEAESepharose CL-6B beads indicating the predominance of negative charges on the hemocyte surface. The hemocytes were incubated with beads suspended in plasma and HCM for enhanced encapsulation response. The beads suspended in HLS showed reduced encapsulation response when compared to control. This clearly shows the opsonic role present in the hemolymph Meretrix casta.